Impaired sensitivity to thyroid hormone is associated with developing non-alcoholic fatty liver disease in euthyroid diabetic subjects - Zhang, Xiaowen; Liu, Jie; Wang, Qian; Han, Chen; Yan, Yu; Xiang, Xinyue; Shen, Shanmei; Feng, Wenhuan (Frontiers in Endocrinology, 2024)
Background and aimsAcquired resistance to thyroid hormone appears to exist in the general population. We aimed to evaluate the association between indices of thyroid hormone sensitivity and non-alcoholic fatty liver disease (NAFLD), and made stratified analyses by diabetic status.MethodsWe included 26,413 participants from a health screening program and 8,246 hospitalized patients with type 2 diabetes. Thyroid Feedback Quantile-based Index (TFQI), thyroid stimulating hormone index (TSHI) and thyrotroph thyroxine resistance index (TT4RI) were calculated. Advanced fibrosis risk was determined using the FIB-4 score. Multivariate logistic regression analysis was performed.ResultsTFQI was associated with an increased risk of NAFLD in patients with diabetes (fourth quartile vs. first quartile: odds ratio [OR]=1.39 and 1.82 in hospitalized and non-hospitalized patients, respectively, both P<0.001) but not non-diabetic participants (OR=0.94, P=0.40). Further adjustment for the homeostasis model assessment of insulin resistance generated similar findings in diabetes (OR=1.27, P=0.025). The TFQI-associated NAFLD risk increase in diabetic patients was confined to NAFLD with low probability of advanced fibrosis (OR 1.42, P=0.001), but not those with intermediate-to-high probability (OR=0.86, P=0.23). Also, TFQI was associated with a significantly lower risk for advanced fibrosis in the diabetic at-risk patients (OR=0.62, P=0.005) but not those non-diabetic at-risk participants, independent of the presence of NAFLD. The association was less significant for TT4RI and TSHI.ConclusionsImpaired sensitivity to thyroid hormone was associated with an increased risk of developing NAFLD but a reduced risk of advanced fibrosis limited to diabetic individuals. Our findings suggest stratified studies of NAFLD based on diabetic status are needed in the future.